6p-10=4p+12

Simple and best practice solution for 6p-10=4p+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p-10=4p+12 equation:


Simplifying
6p + -10 = 4p + 12

Reorder the terms:
-10 + 6p = 4p + 12

Reorder the terms:
-10 + 6p = 12 + 4p

Solving
-10 + 6p = 12 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
-10 + 6p + -4p = 12 + 4p + -4p

Combine like terms: 6p + -4p = 2p
-10 + 2p = 12 + 4p + -4p

Combine like terms: 4p + -4p = 0
-10 + 2p = 12 + 0
-10 + 2p = 12

Add '10' to each side of the equation.
-10 + 10 + 2p = 12 + 10

Combine like terms: -10 + 10 = 0
0 + 2p = 12 + 10
2p = 12 + 10

Combine like terms: 12 + 10 = 22
2p = 22

Divide each side by '2'.
p = 11

Simplifying
p = 11

See similar equations:

| -36x^2+168x-120=0 | | 9p-18=7p+2 | | 7x-17=81 | | 7p-9=2p+11 | | 2x-12=10-9x | | y=1-x^2 | | s^2=6+s(1-9s) | | 8(x+3)+7(x-1)=0 | | 4x-5=-8 | | (x-18)(x-18)=17 | | 24x-16x^2=0 | | 1(x+2)-1(x-2)=4 | | 3(-3+-5y)-2y=8 | | -2y+3x=8 | | 5(x-9)=4(x+5) | | s^2=-24-10s | | X=20-0.4 | | 3(x-9)=3x+27 | | 2(x-5)=2x-10 | | 6w^3+9w^2=0 | | 5n-5=3n+5 | | 9x=3x+24 | | v-9=-9 | | x+5y=-3 | | n+3/7=1/5 | | -10=z+6 | | n-7=-21 | | n+n-19=17 | | 8=y-3 | | z+45=39 | | 13=-11y+4y | | y/16=-3/4 |

Equations solver categories